Literacy Education Model Using the Scientific Approach (Model Pendidikan Literasi Menggunakan Pendekatan Saintifik) - Emah Khuzaemah; Lilik Herawati; Hikmah Uswatun Ummi (Indonesian Language Education and Literature, 2018)
The low literacy of Indonesian students becomes a national issue. As educators are required to be able to fix this problem. An educator should continue to work on finding the right way to increase student literacy. One way that can be done is through the application of the scientific approach. In this study, the scientific approach applied to creative writing learning, students are motivated to improve their reading and writing activities. This study aims to describe the process of literacy learning through the application of the scientific approach, student literacy activities, and the ability to write short stories of students. This research is a classroom action research at SMPN I Palimanan with a purposive sample of class 7A. The data were analyzed in the form of students' ability in writing short stories and student literacy activities with descriptive analytic technique. The results showed an increase in student literacy activities and creativity of students in developing creative ideas through short stories that he wrote.Â Rendahnya literasi pelajar Indonesia menjadi persoalan bangsa. Sebagai pendidik dituntut untuk dapat membenahi persoalan ini. Seorang pendidik hendaknya terus berupaya untuk menemukan cara yang tepat agar dapat meningkatkan literasi siswanya. Salah satu cara yang dapat dilakukan adalah melalui penerapan pendekatan Saintifik. Pada penelitian ini, pendekatan Saintifik diterapkan pada pembelajaran menulis kreatif, siswa dimotivasi untuk meningkatkan aktivitas membaca dan menulisnya. Penelitian ini bertujuan untuk mendeskripsikan proses pembelajaran literasi melalui penerapan pendekatan Saintifik, aktivitas literasi siswa, dan kemampuan menulis cerpen siswa. Penelitian ini merupakan penelitian tindakan kelas di SMPN I Palimanan dengan sampel purposif kelas 7A. Data yang dianalisis berupa kemampuan siswa dalam menulis cerpen dan aktivitas literasi siswa dengan teknik deskriptif analitik. Hasil penelitian menunjukkan adanya peningkatan aktivitas literasi siswaÂ  dan kreativitas siswa dalam mengembangkan ide-ide kreatifnya melalui cerita pendek yang ditulisnya.